Reaction of C-Aroyl-N-Aryl Nitrilimines with Selected Aliphatic Keto-Hydrazones and Keto-Methylhydrazones - A. EL-Sawi, Emtithal; M. Awadallah, Adel; S. Ferwanah, Abdel-Rahman; M. Dalloul, Hany (Asian Journal of Chemistry, 2010)
C-Benzoyl- and C-2-naphthoyl nitrilimines (2) react with methylhydrazones of aliphatic ketones (3, R1 = CH3) to afford the cyclocondensation products 1,2,4,5-tetrazines (4,5). The reaction of simple hydrazones (3, R1 = H) with the same nitrilimines gives the acyclic electrophilic addition products (6, 7), rather than the cyclocondensation tetrazine products.